Adult nephrotic syndrome in the Niger delta sub region: a single centre study at the university of Port Harcourt teaching hospital - Chioma, Pedro C. Emem; Wokoma, Friday S. (International Journal of Advances in Medicine, 2020)
Background: Adult nephrotic syndrome is a common cause of chronic kidney disease globally and in Sub-Saharan Africa. In Nigeria there are only few studies on adult nephrotic syndrome, mostly from the south-western Nigeria and rarely from the Niger delta sub-region of Nigeria. This study aims at contributing to the National data on adult nephrotic syndrome, from the perspective of the Niger delta sub-region. Methods: Retrospective analysis of five-year clinical data (January 2007 to December 2011) of adult nephrotic syndrome patients in the University of Port Harcourt teaching hospital was conducted. Results: Forty-four patients, representing 1% of medical admissions and 7.3% of adult renal cases were seen during the period, with mean age of 27.7±8.5 years. There were 32 males (72.7%). Mean duration of illness was 25.3±30.3months. Peak age group was the 20-29 year age group, accounting for 52.3% of cases. Hypertension was seen in 45.5%. Mean e-GFR was 73.5±33.8 ml/min/1.73m2 with CKD 1-3 constituting 93.2% of cases. Mean 24-hour urinary protein excretion was 13.6±8.4 grams/day. Protein excretion >10grams/day was observed in 65.8% of the patients. Mean total serum protein, albumin and total cholesterol were 51.4±11.7g/dl, 22.5±9.9 g/dl and 8.1±3.0 mmol/L, respectively. Anemia was common (68%) and histology showed MCGN (52.6%), MCD (21.1%), membranous (15.8%) and FSGS (10.5%). Though response to therapy was generally poor, immunosuppressive therapy showed better outcomes. Conclusions: The prevalence and pattern of adult nephrotic syndrome in the Niger delta sub-region is similar to that in other parts of Nigeria. It is predominantly a disease of young adult males with high prevalence of hypertension, and poor histologic categories.